2008
DOI: 10.2136/vzj2007.0060
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Modeling Water Flow in Variably Saturated Soils with SWAP

Abstract: A : IC, internal catchment [domain]; LGM, National Groundwater Model for the Netherlands; MHW, mean high water; MLW, mean low water; SWAP, Soil Water Atmosphere Plant [model]; WP, water productivity.S S : V Z M The Soil Water Atmosphere Plant (SWAP) model simulates transport of water, solutes, and heat in the vadose zone in interac on with vegeta on development. Special features of the model are generic crop growth, versa le top boundary condi ons, macroporous fl ow, and interac on of soil water with groundwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
158
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(164 citation statements)
references
References 51 publications
2
158
0
4
Order By: Relevance
“…Novák et al (2000) attached a FRACTURE module to HYDRUS in which a source term was added to the Richards equation accounting for infiltration from the bottom of the fractures, bypassing matrix bulks. Van Dam (2000), added a crack sub-model to SWAP (van Dam et al, 2008) and Hendriks et al (1999) used a code called FLOCR/AMINO, to study flow and transport phenomenon in shallow and cracked clayey unsaturated-zones in the Netherlands. A model of herbicide transport through the preferential paths was fitted successfully with the improved MACRO version 5.1 (Larsbo et al, 2005).…”
Section: Development Of Flow and Transport Models In Cracking Claysmentioning
confidence: 99%
“…Novák et al (2000) attached a FRACTURE module to HYDRUS in which a source term was added to the Richards equation accounting for infiltration from the bottom of the fractures, bypassing matrix bulks. Van Dam (2000), added a crack sub-model to SWAP (van Dam et al, 2008) and Hendriks et al (1999) used a code called FLOCR/AMINO, to study flow and transport phenomenon in shallow and cracked clayey unsaturated-zones in the Netherlands. A model of herbicide transport through the preferential paths was fitted successfully with the improved MACRO version 5.1 (Larsbo et al, 2005).…”
Section: Development Of Flow and Transport Models In Cracking Claysmentioning
confidence: 99%
“…Specifically, for the unimodal VGM function, the authors reported a value of 0.023 1/cm for the shape parameter a and a saturated hydraulic conductivity K s of 68.7 cm/min. Moreover, the plausible occurrence of film flow in the filter layer, which can support very high flow rates, especially at near-zero matrix potential (Tokunaga, 2009), needs to be contemplated. Under such circumstances, the hydraulic behavior of the material tends to deviate from the typical Richard's type flow, and the optimized parameters attempt to approximate a combination of fingering and film flow that likely occur in this layer.…”
Section: Kriging-based Optimizationmentioning
confidence: 99%
“…The model, previously validated against field scale measurements, was used to investigate the hydraulic response of a green roof to single precipitation events and its hydrological behavior during a two-month period. Metselaar (2012) used the SWAP model (van Dam et al, 2008) to simulate the one-dimensional water balance of a substrate layer on a flat roof with plants. Li and Babcock (2015) used HYDRUS-2D to model the hydrologic response of a pilot green roof system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, eco-hydrological models such as SWAT (Arnold et al 2012), SWIM (Krysanova et al 2005) or SWAP (van Dam et al 2008) were reasonable candidates. They represent catenas and landscape organization in a lumped manner at sub-basin scale.…”
Section: Eco-hydrological Model Options and Selectionmentioning
confidence: 99%
“…IBIS (Kucharik and Brye 2003), CERES (Richie 1998 in Tsuji et al 1998), or Daisy (Abrahamsen and Hansen 2000), the models of the Wageningen-School (Ittersum et al 2003), Sucros (Simple and Universal CROp growth Simulator; Goudriaan and van Laar 1994), WOFOST (WOrld FOod STudies; Boogaard et al 1998) and SWAP (Soil Water Atmosphere Plant; Kroes and van Dam 2003) come closest to meeting these requirements. Moreover, SWAP has been applied for simulations under comparable climatic conditions and for the crops of interest in northern India (van Dam and Malik 2003). The strong hydrological focus of this approach, its comparable physical basis, the existing parameter sets for the crops of our project, availability of the code and previous studies with comparable model set-ups (Pauwels et al 2007) were strong reasons to choose SWAP/ WOFOST.…”
Section: The New Crop Subroutine Based On Swap/wofostmentioning
confidence: 99%